Free Fibular Osteoseptocutaneus Flap for Reconstruction of Giant Ameloblastoma - Rachmat Wiardi; Irra R. W. (Universitas Kristen Maranatha, 2016)
Ameloblastoma is a tumor originating from odontogenic epithelial cells. The tumor islocated in the gray zone between benign and malignant neoplasm. These tumors can occur atany age. Although traditionally divided as solid and cystic ameloblastoma, nearly all showedcystic changes. These tumors are invasive and have a very high recurrence rate. The operativetherapy of choice is radical resection of the affected parts of the jaw, followed byreconstruction. Bridging titanium plate can be used to replace part of lost bone and serves as ameans of reconstruction. Various methods of reconstruction of the mandible can be done byusing a bone graft from the calcaneus, fibula, ribs, scapula, iliac crest, or flap reconstruction.We reported a case of a 18 years old male patient with lump under the tongue that emerged 8years ago, accompanied by eating and speaking difficulty, and shortness of breath. Thediagnosis of mandible ameloblastoma was confirmed by anatomical pathology examination.The patient went through segmental mandibulectomy and free fibular osteoseptocutaneous freeflap with multiple osteotomy. Patients went home with improved condition.Keywords: ameloblastoma, free fibular flap osteoseptocutaneus